Rapid Onset Pressor Response to Exercise in Young Women with a Family History of Hypertension - Matthews, Evan L. (Exp Physiol, 2017)
Hypertensive adults demonstrate atypical increases in blood pressure (BP) and muscle sympathetic nerve activity (MSNA) at the immediate onset of static muscle contraction. However, it is unknown whether these abnormal responses occur in young, otherwise healthy adults at risk for developing future disease, such as those with a family history of hypertension (+FH). We tested the hypothesis that +FH young women have exaggerated increases in BP and MSNA at the onset of static muscle contraction compared to those without a family history of hypertension (-FH). We retrospectively examined beat-by-beat BP and MSNA during the initial 30 seconds of isometric handgrip exercise (30% of maximum voluntary contraction) in 16 +FH (22±2yrs, 22±3kg•m(-2)) and 16 -FH (22±3yrs, 22±3kg•m(-2)) women. Resting mean arterial pressure (MAP; +FH 80±11 vs. -FH 84±13mmHg), MSNA burst frequency (+FH 7±3 vs. -FH 9±5bursts•min(-1)), and burst incidence (+FH 12±4 vs. -FH 12±8bursts•100 heartbeats (-1)) were similar between groups (all P>0.05). Within the first 10 seconds of exercise, changes in MAP (+FH Δ8±6 vs. -FH Δ3±2 mmHg, P<0.05) and HR (+FH Δ8±5 vs. -FH Δ4±4 mmHg, P<0.05) were greater in +FH women. Absolute MSNA burst frequency during the first 30 seconds of exercise was not different between groups (-FH: 7±5 vs. +FH: 9±3 bursts/min). Cardiovascular and sympathetic responses during cold pressor test were not different between groups. These data demonstrate that young women at risk for developing cardiovascular disease exhibit greater changes in BP at the onset of static muscle contraction.